Interesterification of fat blends rich in omega-3 polyunsaturated fatty acids catalysed by immobilized Thermomyces lanuginosa lipase under high pressure - Osório, N.M. (2008)
The interesterification of natural fats will improve certain physical and nutraceutical properties by modification of their acylglycerol profile. In this study, the effect of high pressure in the interesterification kinetics of fat blends, in solvent-free medium, catalysed by a commercial immobilized lipase from Thermomyces lanuginosa was evaluated. Reaction media were ternary blends of palm stearin, palm kernel oil and a concentrate of triacylglycerols (TAG) rich in -3 polyunsaturated fatty acids. Reactions were carried out at 60 ◦C, at 0.1, 50, 100 and 150MPa. The interesterification was followed (i) by the decrease in “Solid Fat Content” values of the blend at 35 ◦C (SFC35 ◦C) and (ii) by the changes in the acylglycerol profile. The biocatalyst presented interesterification activity at least up to 150MPa. Results obtained at 0.1MPa, with no agitation of the reaction medium, were found to be similar to those obtained under high-pressure conditions. The observed decrease in SFC35 ◦C values was accompanied by important changes in the acylglycerol profile. An increase in compounds of low equivalent carbon number (ECN) and in TAG of ECN 44 and 46 were observed. This increase was accompanied by a consumption of TAG of ECN 48 and 50 for all pressure values, and also of trilaurin (ECN = 36) at normal pressure. High pressures seem to affect lipase selectivity towards lauric acid. Batch operational stability tests showed a linear inactivation profile for each pressure. Half-lives of about 15, 6 and 4 h were estimated for the biocatalyst under 0.1, 50 and 150MPa, respectively